What Is Your Faction? Multidimensional Evidence for the Divergent Series As the Basis for a New Model of Personality and Work Life - de Souza, Bruno C.; Roazzi, Antonio (Frontiers in Psychology, 2017)
Introduction: The successful "Divergent" sci-fi trilogy by writer Veronica Roth portrays a dystopian and post-apocalyptic society where the population is divided into five groups called "Factions", each with a specific social role and associated to a specific set of psychological traits. Though fictional, such typology is compelling and may provide a significant contribution to personality studies. Objectives: To investigate the accuracy of the classification of psychological and sociocultural traits into five Factions as described in Divergent and their potential practical usefulness for understanding work life choices and experiences in organizations. Method: A total of 217 Brazilian adult men and women of various ages, socioeconomic status and ethnicities were submitted to measures of several psychological and sociocultural variables, as well as of how strongly they supposedly manifest each Faction. The resulting dataset was studied using Smallest Space Analysis (SSA) and Facet Theory. Results: The Factions were shown not only to be associated to psychological variables in ways consistent with the descriptions from Divergent, but also to be related to specific aspects of one’s work life in organizations. Conclusions: The five Factions conceived by Roth appear to constitute an original set of constructs that are psychologically valid and, at the same time, of practical use in predicting work life choices and experiences. This justifies engaging in future empirical and theoretical work towards a new scientific model of potential practical value.